Awareness of neglected tropical diseases among medical and health sciences students at King Abdulaziz University, Jeddah: a cross-sectional study - Altwaim, Sarah A.; Alsaady, Isra; Gattan, Hattan S.; Alruhaili, Mohammed H.; Alghanmi, Maimonah; Abdala, Shaymaa A.; Kamaludeen, Juriah; Barnawi, Abdulaziz (Bahrain Medical Society, 2023)
Background: Neglected tropical diseases (NTDs) are chronic illnesses that affect people worldwide, especially the poor. Infection prevention and control is cost-effective and long-term by raising NTD awareness. Few studies have examined healthcare providers' knowledge of these infections and parasitic origin diseases in developing and developed countries, as well as in Saudi Arabia. Objectives: To assess medical and health sciences students' awareness of neglected tropical diseases (NTDs) with parasitic origins at King Abdulaziz University in Jeddah. Methods: From February to June 2022, King Abdulaziz University conducted a cross-sectional descriptive survey of 201 medicine and health sciences students. Questions covered NTD awareness, control, and participation. Categorical factors were presented as percentages and frequencies in statistical analysis. Results: The study had roughly equal male and female student participation. Over half of the students didn't know what NTDS was or that Saudi Arabia had NTDs. NTDs were a public health issue in Saudi Arabia, but only 6 of students had seen them. Most Saudi students didn't know about entity control actions. Medical and health students don't understand NTDs or their treatment. Saudi Arabia's health system may be strained by imported diseases due to this gap. Therefore, medical and health sciences students must be educated about NTDs.